Study on Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and Antioxidant Activities of Urtica Dioica of Nepalese Origin - Bhatt, Bishan Datt; Parajuli, Gagan Chandra (Journal of Nepal Chemical Society, 2017)
available with fulltext.